Management School Curriculum of Inclusion In the Kindergarten the Talents of Semarang - Fikriyyah, Lina; Astuti, Henny Puji (Jurusan PGPAUD FIP UNNES, 2017)
Management curriculum is one of the primary management substances at school. Basic princeples of curriculum management is tryingto let the learning process can be run well. Talents kindergarten is inclusion in Semarang who receive learners with the various needs of children without distinction, either normal or children in need special. Formulation of the problem in the writing of this is how the planning, implementation, and evalution of the curriculum in the kindergarten school of Semarang Talents as inclusion. This type of research is qualitative research in methods of case studies. Data collextion method using observation, interview, and documentation. The data obtained are examined the validity of the data with the triangulation of sources and triangulation methods. Data were analyzed with the interactive model of data analysis, techniques Miles and Huberman. Based on data analysis, planning curriculum in kindergarten Talents Semarang arranged through work meetings between the principal and the teacher to design a learning device refers to the 2013 curriculum, early childhood education program that includes annual, semester, weekly, and daily. For children in need of special school still in the drafting stage of Talents as the school inclusion is basiclly almost the same with other conventional school. The curriculum used in reference to 2013 curriculum, early childhood education. The implementation of the curriculum through the learning process includes the structuring materials and tool main, welcoming the presence of children, play facilities, the line enters the classroom, morning devotion, transition, opening activities, the core activity of playing on central, eat together portlnd, closing activities, and the evaluation activities on that day. Curriculum evaluation activitites carried out regularly once a week by teachers and principals on Friday, while reports of child development reported to parents each semester through report cards.